Intra-articular migration of the tibial bone plug during anterior cruciate ligament reconstruction with bone-patellar tendon-bone autograft: a case series - Jung, Woon-Hwa; Yadlapalli, Saipramod; Kim, Dong-Hyun; Singh, Mukul Kumar (International Journal of Research in Orthopaedics, 2025)
Bone-patellar tendon-bone (BPTB) autografts are a preferred choice for anterior cruciate ligament (ACL) reconstruction due to their potential for reliable bone-to-bone healing. However, technical errors can lead to significant complications. This report presents a series of three cases where the tibial bone plug of a BPTB autograft migrated into the intra-articular space. Postoperative analysis identified that proximal displacement of femoral bone plug, divergence of the interference screw during femoral screw fixation was the primary cause. This led to proximal migration of the graft, increase of tension, and subsequent displacement of the tibial bone plug. These cases underscore the critical importance of meticulous surgical technique, particularly in ensuring accurate screw placement to prevent graft migration.